Book Review: Experimentelle Archäologie in Europa, Jahrbuch 2016 - Milica Tapavički-Ilić (EXARC, 2017)
The periodical "Experimentelle Archäologie" is issued by Gunter Schöbel and the "Europäische Vereinigung zur Förderung der experimentellen Archäologie", together with Pfahlbaumuseum Unteruhldingen from Germany. Issue no. 15 includes 223 pages of text, with numerous colour photographs. The content of the issue is divided into three main parts: Experiment und Versuch (Experiment and Attempt), Rekonstruierende Archäologie (Reconstruction Archaeology) and Vermittlung und Theorie (Interaction and Theory).